Cultural Heritage and Religious Phenomenon between Urbicide and Cancel Culture: The Other Side of the Russian–Ukrainian Conflict - Botti, Federica (Religions, 2023)
The Russian–Ukrainian conflict, in addition to causing an unacceptable loss of human life, is straining the integrity of Ukraine’s cultural heritage, despite the fact that both countries involved are parties to the 1954 Hague Convention for the Protection of Cultural Property in the Event of Armed Conflict and its First Protocol. Churches are one of Ukraine’s most important historical assets, as well as symbolic places of Orthodox religious identity common to both the invaders and the invaded. The destruction of these places and their deliberate damage on the part of both sides appear to be part of a more general conflict concerning internal disagreements between Russian and Ukrainian Orthodoxy, which, in turn, reflect two different historical views of the Russian–Ukrainian relationship. A brief reconstruction of relations between the Orthodox Churches operating on the territory of Ukraine demonstrates how religious affiliation has affected the conflict, causing it to become decisive and deeply divisive, so much so that the Patriarchate of Moscow has become an active part of the conflict. This circumstance favours the hypothesis that it is precisely the religious cultural heritage that is most at risk of deliberate destruction. The Russians, by destroying the symbolic places of Ukrainian religious identity (urbicide), affirm the spiritual unity of the Russian and Ukrainian peoples. For their part, the Ukrainians attempt to erase the Russian presence and the common religious cultural roots by destroying buildings of worship dear to the tradition of the Moscow Patriarchate (cancel culture). They reject the imperial traditions of Russia and, at the same time, claim an independent Church. The question arises as to whether the reconstruction process following the war will take into account the original cultural–religious identities, or whether it will take the opportunity to adopt a new (also) religious identity instead, and whether the old and new instruments offered by law are adequate.